Behavior of a Circular Footing resting on Sand Reinforced with Geogrid and Grid Anchors - Helis, Rima; Mansouri, Tarek; Abbeche, Khelifa (Engineering, Technology & Applied Science Research, 2023)
This study used finite element analysis to investigate the influence of using two reinforcing systems, the geogrid and the grid anchor, on the bearing capacity of a circular footing resting on sand. The parameters studied were the effect of the number of reinforcement layers (N), the depth ratio of the topmost layer of reinforcement (u/d), the vertical spacing ratio between consecutive layers (h/d), and the effect of reinforcement length (L). The results showed that the reinforcement layout had a very significant effect on the behavior of the reinforced sand foundation. The maximum bearing capacity for single-layer inclusion was obtained when reinforcement was placed at a depth of u/d=0.42. Bearing capacity was also found to improve when increasing the number of reinforcement layers from 1 to 3. Additionally, the analysis showed that the sand reinforced by grid anchors performed better than that reinforced by geogrid. Finally, an improvement in load capacity was obtained by increasing the length of the inclusions, and the optimal length of the reinforcements was determined at 5d for both inclusions.